Abundance of organohalide respiring bacteria and their role in dehalogenating antimicrobials in wastewater treatment plants. (15th August 2020) - Zhao, Siyan; Rogers, Matthew J.; He, Jianzhong
Abstract: Anthropogenic organohalide contaminants present in wastewater treatment plants (WWTPs) often remain untreated and can be discharged into the environment. Although organohalide respiring bacteria (OHRB) contribute to the elimination of anthropogenic organohalides in natural anaerobic environments, reductive dehalogenation by OHRB in mainstream WWTPs remains poorly understood. In this study, we quantified OHRB during a long-term operation of a municipal WWTP with short hydraulic and sludge retention times (3 h and 1.5–5 days, respectively). The obligate OHRB were detected at high levels (averaging 2.56 ± 1.73 × 10 7 and 3.11 ± 1.16 × 10 7 16S rRNA gene copies/ml MLSS sludge in anoxic and aerobic zones, respectively) over the entire sampling period and throughout the wastewater treatment train. Microcosms derived from mainstream activated sludge contained an unidentified member of the Dehalococcoides genus that metabolically dechlorinated triclosan, used as a representative emerging organohalide antimicrobial, to diclosan, suggesting the potential of anaerobic degradation of emerging contaminants in WWTPs. To further understand the mechanisms for such antimicrobials' removal, an investigation of dechlorination of triclosan by Dehalococcoides strains was conducted. Dechlorination of environmentally relevant concentrations of triclosan to diclosan was observed in Dehalococcoides mccartyi strain CG1, yielding 4.59 ± 0.34 × 10 8  cells/μmole Cl − removed at a rate of 0.062 μM/day and a minimal inhibitory concentration of 0.5 mg/L. Notably, both the tolerance of strain CG1 to triclosan and the rate of triclosan dechlorination increased when CG1 was cultured in the presence of both triclosan and tetrachloroethene. Taken together, our results suggest that anaerobic degradation of organohalide antimicrobials might be more prevalent in mainstream WWTPs than previously speculated, though the low growth yields that are supported by triclosan dechlorination seem to indicate that other organohalide substrates could be necessary to sustain OHRB populations in these systems. Graphical abstract: Image 1 Highlights: Biological removal should be considered in determining emerging contaminants' fate. Organohalide respiring bacteria found in high abundance in mainstream municipal WWTP. Organohalide respiring bacteria contribute to organohalide antimicrobials' removal. Dehalococcoides mccartyi strain CG1 dechlorinates triclosan via RDase PcbA1.